Fiscal Decentralization and Economic Growth in Morocco: A Panel Cointegration Analysis - Miri, Meriem; Taacha, El Hassan; Benatia, Mohamed Ayman (International Journal of Economics and Financial Issues, 2018)
This article focuses on the effects of fiscal decentralization on economic growth in Morocco, taking into account three dimensions: expenditure decentralization, revenue decentralization and the composite of these two indices. It uses a co-integration panel approach to separate long run effects from short run dynamics; By using and revising the set of data generally used in these empirical analyses. The results show that fiscal decentralization can lead to significant long-term economic growth (particularly significant for revenue decentralization), but in the short-term, this leads to a decrease in economic growth. Indeed, short-term results show that fiscal decentralization generates in the very short term a decrease in economic growth before improving over time until reaching a long-term increase between 2003 and 2014 in Morocco. Keywords: fiscal decentralization, economic growth, Morocco JEL Classifications: C2, H7